Farmers’ Perception and Adoption of Abiotic Stress Tolerant Rice Varieties in Rain-fed Lowlands of North Eastern Uttar Pradesh - Ravindra and Alka Singh, (Indian Journal of Extension Education, 2017)
The study is based on field level data collected from submergence-prone areas of rain fed lowlands of eastern UttarPradesh. Two districts viz. Gorakhpur and Siddharthnagar were selected purposively on basis area and production.The ultimate sample size was 120 farmer households. Qualitative and quantitative information on rice productionpractices for the kharif season of 2015-16 was collected using structured interview schedules.Farmers were askedto compare the relative performance of improved and traditional varieties being grown in the village. The varietaldiversity index (VDI) was employed to know rice varietal diversity at farm level in the region.An analysis of farmers’preferences and perceptions showed that majority of sample farmers cultivating Sarjoo-52 (89%) and Kalanamak(100%) preferred these varieties for their good eating quality. However, Swarna Sub-1 and Samba Masuri Sub-1were preferred by majority of farmers (84 per cent) for higher yield performance during field submergence conditions.